BAP1 Tumour Predisposition Syndrome Due to Whole BAP1 Gene Deletion. (13th September 2022) - Pandithan, Dinusha; Klebe, Sonja; McKavanagh, Grace; Rawlings, Lesley; Yu, Sui; Nicholl, Jillian; Poplawski, Nicola
Abstract : BRCA-1-associated protein-1 (BAP1) tumour predisposition syndrome (BAP1-TPDS) is a dominant hereditary cancer syndrome. The full spectrum of associated malignancies is yet to be fully characterised. We detail the phenotypic features of the first reported family with a whole BAP1 gene deletion. This report also adds to the emerging evidence that the rhabdoid subtype of meningioma is a part of the clinical spectrum of this tumour predisposition syndrome.